Hyperfine field and isomer shift evolution in hydrogenated Nd-Fe-B alloy - Saccone, Fabio Daniel (2001)
RE₂Fe₁₄B (RE=rare earth) materials are capable of absorbing hydrogen to form a stable solid solution at room temperature. Hydrogenation produces a number of significant changes in the hyperfine interactions. In this work, 57Fe Mossbauer effect spectroscopy and X-ray diffraction measurements were performed on Nd₁₄.₀₁Hf₀.₀₈Fe₇₈.₉₁B₇.₀₀ alloys submitted to thermal treatment in hydrogen atmosphere. A non-linear increase of the hyperfine fields and isomer shifts with hydrogen concentration was observed. The hyperfine parameters of the 8j₁ site exhibit a rather different evolution than those experienced by the other major sites (8j₂, 16k₁, 16k₂). The origin of the hyperfine field enhancement is analyzed in terms of volume expansion and H nearest neighbors to the Fe sites. A linear expression on these two effects to give account of isomer shift evolution for 8j₁ site is given.